2021
DOI: 10.3390/vaccines9111222
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of COVID-19 Vaccination in the Elderly: A Cross-Sectional Study in Southern Italy

Abstract: In Italy, at the end of 2020, a voluntary immunization plan against COVID-19 was introduced, involving elderly among the first target categories. The aim of this study was to assess, through an online questionnaire, the acceptance of COVID-19 vaccination in a sample of older adults from southern Italy. Of a total of 1041 respondents (41.7% males, mean age 76.6 ± 6.5), 965 (92.7%) were vaccinated or willing to be vaccinated against COVID-19, although less than half of the sample was favorable to vaccinations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
93
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 30 publications
2
93
2
2
Order By: Relevance
“…The implication of a higher susceptibility of the older people towards COVID-19 may have culminated in a more heightened awareness of it, which translated into an adequate knowledge level [44]. Evidently, an Italian study predominantly involving elderly people (mean age 76.6 ± 6.5) demonstrated a very high extent of positive attitudes and acceptance (92.7%) towards COVID-19 vaccination [45]. Moreover, the tendency of the older adults to read newspapers and follow cable channels regularly may have further contributed to their superior understanding of COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…The implication of a higher susceptibility of the older people towards COVID-19 may have culminated in a more heightened awareness of it, which translated into an adequate knowledge level [44]. Evidently, an Italian study predominantly involving elderly people (mean age 76.6 ± 6.5) demonstrated a very high extent of positive attitudes and acceptance (92.7%) towards COVID-19 vaccination [45]. Moreover, the tendency of the older adults to read newspapers and follow cable channels regularly may have further contributed to their superior understanding of COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…A global study conducted in 19 countries in June 2020 found that 71.5% of participants were likely to get vaccinated against COVID-19 [11]. A recent study conducted among older adults from southern Italy reported that 92.7% participants were willing to be vaccinated, with a similarly high acceptance rate of 91.9% reported among Italian undergraduate students [12,13]. Comparable findings were observed in other countries, including Canada, Saudi Arabia, the United States, and China, where acceptancy rates ranged from 67% to 91% [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we observed that, after the first wave, the general web interest in the pandemic has steadily declined until nowadays. As noted in other papers, web interest has shifted to related and more practical topics 7/14 including smart working and learning 22,23 , drug treatments 24 , vaccines 17,25 , and green-pass 26 . A similar but in some respects worse scenario was observed for COVID-19 variants of concern (VOCs).…”
Section: Discussionmentioning
confidence: 91%